Methylene blue used in the treatment of refractory shock resulting from drug poisoning. (January 2014) - Fisher, J.; Taori, G.; Braitberg, G.; Graudins, A.
<x xml:space="preserve">Abstract</x> Background. Methylene blue inhibits the nitric oxide–cyclic guanosine monophosphate (NO–cGMP) pathway, decreasing vasodilation and increasing responsiveness to vasopressors. It is reported to improve haemodynamics in distributive shock from various causes including septicaemia and post-cardiac surgery. Reports of use in overdose are limited. We describe the use of methylene blue to treat a case of refractory distributive shock following a mixed drug poisoning. Case details. A 41-year-old male presented following reported ingestion of 18 g extended-release quetiapine, 10 g controlled-release carbamazepine, 240 mg fluoxetine, 35 g enteric-coated sodium valproate and 375 mg oxazepam. He was comatose and intubated on presentation. Progressive hypotension developed. Echocardiogram revealed a hyperdynamic left ventricle, suggesting distributive shock. The patient remained hypotensive despite intravenous fluid boluses, escalating vasopressor infusions. Arterial blood gas revealed metabolic acidaemia and high lactate. Methylene blue was administered as loading-dose of 1.5 mg/kg and continuous infusion (1.5 mg/kg/h for 12 h, then 0.75 mg/kg/h for 12 h) resulting in rapid improvement in haemodynamic parameters and weaning of vasopressors. Serum quetiapine concentration was 18600 ng/mL (30–160 ng/mL), collected at the time of peak toxicity. Conclusion. Severe quetiapine poisoning produces hypotension primarily from alpha-adrenoreceptor antagonism. Methylene blue may have utility in the treatment of distributive shock resulting from poisoning refractory to standard vasopressor therapy.